The Development of the Silk Industry in the Ottoman Bursa: An Analysis of Periodization - Özgür TEOMAN; Cumali BOZPİNAR (Gazi Akademik Bakış)
There are a limited number of studies on the periodization analysis of the historical development of a single sector in Ottoman economic history literature. This study puts forward a periodic analysis of the sector in order to reveal the economic development characteristics of the Ottoman Bursa silk industry. In the study, four turning points where the transformation took place in terms of roduction relations and conditions were determined and the periodic analysis focused on these four periods. The city of Bursa became a silk production and trade center after it came under Ottoman rule. The fluctuations in the demand level of European countries for fabrics between the second half of the XVIth century and the first quarter of the XIXth century caused the silk industry to enter an unstable process, despite maintaining its commercial importance. With the inclusion of the Ottoman country in the center-periphery relationship after 1830, the existing production relations in the sector underwent a process of transformation. The transformation aspect in this century was deindustrialization in silk weaving and increased specialization in raw silk production as a result of technological development and the sector passed to the capitalist stage, provided that it was limited to raw silk production. The last breaking point in silk sector was the transfer of raw silk tax revenues to the Ottoman Public Debt Administration (Düyun-ı Umumiye Administration).